2023
DOI: 10.1007/s10681-023-03268-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping of genes for anthocyanin and flavonoid contents in Vietnamese landraces of black rice

Cuong Hung Pham,
Tuyen Duc Do,
Hoa Thi Lan Nguyen
et al.

Abstract: Pigmented rice is desirable in healthy human diets because of potential health benefits compared to white rice. Based on the high diversity of Vietnamese black rice landrace, mapping the loci and predicting putative candidate genes for anthocyanin and flavonoid contents in these landraces would be useful to support the improvement of pigmented rice. A panel of 94 black rice accessions from the National Plant Genebank of Vietnam was analyzed to determine the anthocyanin and flavonoid levels in the whole grain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
2
0
0
Order By: Relevance
“…In line with previous reports (Chen et al 2016;Pham et al 2023), we found that secondary metabolite levels showed the highest average phenotypic variation across all metabolic traits, whereas variation for growth parameters was lowest. For secondary metabolites, high variation in tissue concentration was explained by their low trait complexity (Pham et al 2023;Haghi et al 2022;Chen et al 2014). Whereas primary metabolites and growth seem to be regulated by many small effect loci, secondary metabolites are often controlled by just a few major-effect loci (Chen et al 2014;Chen et al 2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with previous reports (Chen et al 2016;Pham et al 2023), we found that secondary metabolite levels showed the highest average phenotypic variation across all metabolic traits, whereas variation for growth parameters was lowest. For secondary metabolites, high variation in tissue concentration was explained by their low trait complexity (Pham et al 2023;Haghi et al 2022;Chen et al 2014). Whereas primary metabolites and growth seem to be regulated by many small effect loci, secondary metabolites are often controlled by just a few major-effect loci (Chen et al 2014;Chen et al 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Previous GWAS conducted on complex traits highlighted, that the success in identifying genetic associations greatly depends on sample size and phenotypic variation (Schizophrenia Working Group of the Psychatric Genomics Consortium 2014; Duncan et al 2019;Chen et al 2014). In line with previous reports (Chen et al 2016;Pham et al 2023), we found that secondary metabolite levels showed the highest average phenotypic variation across all metabolic traits, whereas variation for growth parameters was lowest. For secondary metabolites, high variation in tissue concentration was explained by their low trait complexity (Pham et al 2023;Haghi et al 2022;Chen et al 2014).…”
Section: Discussionsupporting
confidence: 88%